ANALISIS KEMAMPUAN BERPIKIR REVERSIBLE SISWA SMP DALAM MENYELESAIKAN MASALAH SISTEM PERSAMAAN LINEAR DUA VARIABEL - Nurlatifah, Mita; Lukman Hakim, Dori (Universitas Bhinneka PGRI, 2024)
ability to think reversible or can also be called reversibility is the ability to build a reversible two-way correlation. The ability to think reversible is essential because this ability can affect problem solving. Therefore, this article is made to describe the reversible thinking ability of grade VIII high school students in solving mathematical problems on the material of the two-variable linear equation system of the graph method. This study uses a descriptive analysis method with a qualitative approach. The subjects used in this study were 15 junior high school students grade VIII. This reversible thinking can be analyzed based on two indicators, namely go forward and reverse. The data collection process is carried out through the provision of tests. The results obtained from this study showed that the reversible thinking ability of the students was still low, Because there are still many of these students who do not have adequate ability in reversible thinking so that they cannot solve problems properly.